The Exploration of Hydrocarbons and Mining & Energy Resources Using Non-Seismic Methods - Nuclear Magnetic Resonance Technology - Zamora Santacruz, Mario Fernando; RUIZ, Mario; OSORNO, Jose (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Nuclear Magnetic Resonance-based technology is a geophysical method used in the exploration of hydrocarbons and other mineral resources, by studying electromagnetic signals from natural sources. The foregoing method has three phases: the first phase encompasses the identification of areas where hydrocarbons or other minerals are present at a regional level, using remote sensors; the anomalies identified are studied in detail in the second phase, during which the passive acquisition of electromagnetic signals on the surface with under 30m spacing be- tween points allows demarcating the areas with the highest and lowest intensity, to finally obtain stratigraphic columns at points selected after measuring the basic parameters using Vertical Probing with Electro – Resonance. The study conducted for Agencia Nacional De Hidrocarburos (ANH) evaluated a total of 1083 Km2 spread over five areas whose topography, climate and vegetation restricted the acquisition of geological and geophysical data with traditional methods. Two of the five polygons are located in the part of the Chocó basin called Ánimas (163 km2) and Istmina (344 km2) while Timbiquí (159 km2), Remolino (200 km2) and Guayacana (217 km2) are in the Tumaco basin. The results of the satellite stage included the identification of 178 km2 of liquid hydrocarbon type anomalies in the Choco basin and 22 km2 of gaseous hydrocarbon-type anomalies in the Tumaco basin. The anomaly located in Animas was chosen for the field stage. It was detailed by demarcating the areas with the highest and lowest intensity, in which vertical probing took place, allowing for the in-depth characterization of nine parameters (H2O, CaCO3, Si, C10 H22, CH4, C21H44, Clays, Albite, Anorthite) in up to 4,000 m, identifying intervals showing a significant presence of hydrocarbons at 3,280 ft, 6,950 ft and 12,210 ft with a 36 ft.-average thickness, and an estimated basement depth of 12,650 ft. The correlation with seismic data allowed confirming the results, thus proving that the use of non-seismic methods in exploration and prospection processes allow for a better understanding of petroleum systems, while reducing uncertainty and exploratory hazards